THE ORIGINS OF THE ORIGIN AND DEVELOPMENT OF THE MYTHOLOGICAL WORLDVIEW IN THE ART OF ANCIENT CHINA - Искендеров, Анар (SSD Journal, 2022)
China is one of the most ancient civilizations of mankind. Ancient Chinese art and culture have deep spiritual traditions that arose from the fusion of various ethno-cultural values. The art and culture of ancient China are rightfully considered one of the most striking and unique phenomena in the history of human civilization. Since the fifth millennium, the first agricultural centers have appeared in ancient China. It should be noted that the very first mythological and cosmological worldviews of ancient China are connected with the ancient Chinese agricultural culture. Geometric and floral ornaments, zoomorphic and anthropomorphic images that adorn ancient Chinese ceramics of the Neolithic era reflect the myths and rituals of the ancient Chinese. In the middle of the II millennium BC, the Yin civilization was formed in the Yellow River basin. The Yin period in the history of ancient Chinese culture marks a huge progress in many areas of ancient Chinese society. It is also noteworthy that in the decorative and applied art of ancient China of the Yin period, completely new and different art products with elements and motifs of the "animal" style appear in their forms and compositional content. Many researchers believe that the ancient Chinese animal style could have originated and developed under the influence of neighboring nomadic tribes and peoples, as a result of military and trade contacts. Objects with zoomorphic images and compositions that relate to the art of Ancient China of the Han period are carriers of the aesthetic principles of “steppe animalismˮ. These artistic images made in the “animal style” have a high level of decorative stylization, which are characteristic of Ancient Scythian and Hunnic art. Ancient Chinese art, unique both in its ancient semantics and in the style of depicting artistic images, is a phenomenal and still not fully explored phenomenon